Answers

2016-01-17T20:15:11+05:30
{[(3/5)^9 × (3/5)^3] / [3/5]^15} / (3/5)^3
= [(3/5)^(9+3)] / [(3/5)^15] / (3/5)^3         {∵ a^n × a^m = a^(n+m)}
= [(3/5)^12] / [(3/5)^15] × (3/5)^3)]
= (3/5)^12 / [(3/5)^(15+3)]                       {∵ a^n × a^m = a^(n+m)}
= (3/5)^12 / (3/5)^18
= (3/5)^(12-18)                                        {∵ (a^n)/(a^m)  = a^(n-m)}
= (3/5)^-6
= 3^ -6 / 5^ -6                                          {∵ (a/b)^n = (a^n) / (b^n)}
=(1/3^6) / (1/5^6)                                    {∵   a^ -n = 1/(a^n)}
= 5^6/3^6

0